PREFACE - KOVÁCS, András Donát (Discussion Papers, 2011)
Centre for Regional Studies, Hungarian Academy of Sciences has organised the third East-Central European Regional Seminar – ECERS 2010 – in the city of Pécs. This conference was an important occurrence of the co-operation between Polish and Hungarian researchers. The aim of the seminar was to support the initiative of Warsaw Regional Forums and expand the Polish-Hungarian Geographical Seminars. This meeting aimed to highlight different aspects, spatial issues and problems of East-Central European localities. The papers in this volume address the contemporary processes and conflicts of localities, especially local opportunities; features of specific areas, environmental and social problems. They draw attention to the new opportunities of local development and the unique potentials of bottom up initiatives. The studies of the present volume are published with the intention to promote a better understanding of the phenomena and the processes of the localities in East–Central–European countries.